Fatty acid oxidation: An emerging facet of metabolic transformation in cancer - Ma, Yibao; Temkin, Sarah M.; Hawkridge, Adam M.; Guo, Chunqing; Wang, Wei; Wang, Xiang-Yang; Fang, Xianjun (Cancer letters, 2018)
Cancer cells undergo metabolic reprogramming such as enhanced aerobic glycolysis, mutations in the tricarboxylic acid cycle enzymes, and upregulation of de novo lipid synthesis and glutaminolysis. These alterations are pivotal to the development and maintenance of the malignant phenotype of cancer cells in unfavorable tumor microenvironment or metastatic sites. Although mitochondrial fatty acid β-oxidation (FAO) is a primary bioenergetic source, it has not been generally recognized as part of the metabolic landscape of cancer. The last few years, however, have seen a dramatic change in the view of cancer relevance of the FAO pathway. Many recent studies have provided significant evidence to support a “lipolytic phenotype” of cancer. FAO, like other well-defined metabolic pathways involved in cancer, is dysregulated in diverse human malignancies. Cancer cells rely on FAO for proliferation, survival, stemness, drug resistance, and metastatic progression. FAO is also reprogrammed in cancer-associated immune and other host cells, which may contribute to immune suppression and tumor-promoting microenvironment. This article reviews and puts into context our current understanding of multi-faceted roles of FAO in oncogenesis as well as anti-cancer therapeutic opportunities posed by the FAO pathway. •FAO emerges as a new aspect of metabolic transformation in cancer.•Cancer cells rely on FAO for growth, stemness, drug resistance and metastasis.•FAO is reprogrammed in cancer and cancer-associated immune and other host cells.•FAO is druggable given the differential dependence of cancer and normal tissues.•FAO inhibitors including those for other ailments offer new anti-cancer therapies.